Positive margin rates and predictors in transoral robotic surgery after federal approval: A national quality study. Issue 9 (6th May 2019) - Hanna, Jonathan; Morse, Elliot; Brauer, Philip R.; Judson, Benjamin; Mehra, Saral
Abstract: Background: Purpose of the study is to assess nationwide margin performance in oropharynx transoral robotic surgery (TORS). Methods: Retrospective review of the National Cancer Database. Results: Two thousand six hundred sixty‐one patients were included. The national positive margin rate (PMR) was 16.9%. High‐volume facilities had a lower PMR than low‐volume facilities (12.7% vs 21.9%; P < .001). Patients with disease of the tonsil had a lower PMR (15.7%) than base‐of‐the‐tongue (18.2%; P = .14). PMR increased with T classification (T1 = 13.0%, T2 = 17.1%, T3 = 28.2%, T4a = 45.9%, T4b = 58.3%; P < .001). On multivariable regression, factors associated with margin status included only lymph‐vascular invasion (1.63[1.13‐2.36]; P = .01), high volume (0.57[0.36‐0.92]; P = .005), and T classification (as compared to T1, T2: 1.50[1.03‐2.18], T3: 3.11[1.77‐5.46], T4a: 7.03[2.95‐16.75], T4b: 6.72[1.26‐35.93]; P < .001). Conclusions: National PMR is 16.9%, substantially higher than reported in high‐volume TORS centers. There is a linear association between positive margins and T classification, with T3 and T4 PMRs exceeding 28%. High‐volume facilities are half as likely to yield positive margins compared to low‐volume facilities. There was no association between human papilloma virus status, tumor subsite, or academic facility status and positive margins.